2022
DOI: 10.3847/psj/ac7fa1
|View full text |Cite
|
Sign up to set email alerts
|

Pre-encounter Predictions of DART Impact Ejecta Behavior and Observability

Abstract: We overview various efforts within the DART Investigation Team’s Ejecta Working Group to predict the characteristics, quantity, dynamical behavior, and observability of DART impact ejecta. We discuss various methodologies for simulation of the impact/cratering process with their advantages and drawbacks in relation to initializing ejecta for subsequent dynamical propagation through and away from the Didymos system. We discuss the most relevant forces acting on ejecta once decoupled from Dimorphos’s surface and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 71 publications
3
26
0
Order By: Relevance
“…Various observations suggested that the ejecta were dominated by millimeter-to centimeter-sized particles. The ejecta velocity is about 0.2 m s −1 , comparable to the bulk velocity of the expected DART ejecta (Fahnestock et al 2022). The dust size frequency distribution of the ejecta of P/2010 A2 was estimated to have a power-law index of −3.3 to −3.5 based on the modeling of radiation pressure.…”
Section: Characterization Of the Ejecta Particlesmentioning
confidence: 60%
See 2 more Smart Citations
“…Various observations suggested that the ejecta were dominated by millimeter-to centimeter-sized particles. The ejecta velocity is about 0.2 m s −1 , comparable to the bulk velocity of the expected DART ejecta (Fahnestock et al 2022). The dust size frequency distribution of the ejecta of P/2010 A2 was estimated to have a power-law index of −3.3 to −3.5 based on the modeling of radiation pressure.…”
Section: Characterization Of the Ejecta Particlesmentioning
confidence: 60%
“…But considering that it is in the main asteroid belt, where the average relative velocity is about 4-5 km s −1 (Farinella & Davis 1992;Bottke et al 1994), its impact velocity is probably comparable to the DART impact velocity. The only significant difference between the P/2010 A2 impact and the DART impact is the much larger impactor for the former, which was estimated to be tens of meters in radius based on the ejecta mass estimate of about 10 7 -10 8 kg (Jewitt et al 2010), roughly proportionally higher than the expected ejecta mass for DART impact (10 6 -10 7 kg; Fahnestock et al 2022). Therefore, the ejecta from P/2010 A2 provides the best analog to the DART ejecta in terms of the ejecta particle size and size distribution.…”
Section: Characterization Of the Ejecta Particlesmentioning
confidence: 89%
See 1 more Smart Citation
“…Importantly, ejecta curtains will look different as impact velocity and material properties are varied. The full details of the effects of ejecta curtains are well studied and presented in more detail in Fahnestock et al (2022). Ejecta plume simulations using information from shock physics codes as input conditions show that ejecta particle dynamics are sensitive to initial ejection parameters such as orientation and ejection velocity (Ivanovski et al 2020).…”
Section: Deflection Parameters: Crater and Ejectamentioning
confidence: 99%
“…The timing of the close approach flyby would allow LICIACube to be able to observe some if not all of the DART crater formation process, but the ejecta plume may obscure LICIACube's view of Dimorphos' surface. The rate of the observed evolution will depend mostly on the strength (or lack thereof) and porosity of the target (Fahnestock et al 2022). If the target tends stronger and crater formation is complete before closest approach (where the curtain is seen to separate from the crater rim), it will be possible to determine some of the surface geological properties from the crater diameter and possibly its depth.…”
Section: Observing the Dart Cratermentioning
confidence: 99%